2015
DOI: 10.1097/mib.0000000000000409
|View full text |Cite
|
Sign up to set email alerts
|

Use of Endoscopic Ultrasound to Guide Adalimumab Treatment in Perianal Crohnʼs Disease Results in Faster Fistula Healing

Abstract: Rectal EUS-guided ADA therapy for CD perianal fistulas showed an initial benefit at 24 weeks, which was lost at week 48. This is likely due to small sample size and higher fistula closure in the controls. However, the faster rate of fistula resolution is a clinically significant finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Three studies (3 retrospective reviews of prospectively collected data reported by the same first author, perhaps with overlapping populations, and examining treatment with some combination of an anti-TNF-α [agent not specified] plus azathioprine and/or antibiotics[ 24 - 26 ]) reported clinical remission rate and radiological remission rate, one retrospective study (examining fibrin glue with or without adult stem cells) included Magnetic resonance imaging (MRI) results as part of their definition of remission[ 27 ], and two studies (one prospective trial of adalimumab and one retrospective study examining infliximab plus other medications such as 6-mercatopurine, azathioprine, methotrexate, and/or antibiotics) provided rates for both clinical and endoscopic ultrasound-confirmed remission[ 28 , 29 ]. Overall, only a small proportion of patients with CD and CPF treated with anti-TNF-α (agent not specified) achieved radiological healing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies (3 retrospective reviews of prospectively collected data reported by the same first author, perhaps with overlapping populations, and examining treatment with some combination of an anti-TNF-α [agent not specified] plus azathioprine and/or antibiotics[ 24 - 26 ]) reported clinical remission rate and radiological remission rate, one retrospective study (examining fibrin glue with or without adult stem cells) included Magnetic resonance imaging (MRI) results as part of their definition of remission[ 27 ], and two studies (one prospective trial of adalimumab and one retrospective study examining infliximab plus other medications such as 6-mercatopurine, azathioprine, methotrexate, and/or antibiotics) provided rates for both clinical and endoscopic ultrasound-confirmed remission[ 28 , 29 ]. Overall, only a small proportion of patients with CD and CPF treated with anti-TNF-α (agent not specified) achieved radiological healing.…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of adalimumab-treated patients that achieved complete cessation of drainage varied. The complete response rate after adalimumab treatment was 88% at 48 wk among a subset of nine patients enrolled in a randomised prospective study conducted in the United States (US) who underwent assessments by endoscopic ultrasound every 12 wk and was 73% among 11 control patients who received standard of care without endoscopic ultrasound[ 28 ]. Complete response was 28% among 38 CD patients with CPF at 12 mo in a retrospective multicentre study conducted in Spain[ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, endoscopic ultrasound (EUS)76 can provide onsite adjunct assessment of perianal fistulas, sinuses, abscesses and demonstrate local lymphadenopathy. The same endoscope may be used in vaginoscopy to assess rectovaginal or pouch-vaginal fistulas.…”
Section: The Role Of Endoscopy In the Management Of Perianal Fistulasmentioning
confidence: 99%
“…Anti-TNF therapy has been shown to be an effective treatment for closure of perianal fistulizing CD[65]. Infliximab or adalimumab step up therapy for CD guided by assessment of disease severity by anal ultrasound is associated with a high rate of fistula closure[86]. …”
Section: Surgical Options For Perianal CDmentioning
confidence: 99%